2012
DOI: 10.1007/s00441-011-1321-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of expression patterns of AQP4, dystroglycan, agrin and matrix metalloproteinases in human glioblastoma

Abstract: In human glioblastoma, the blood-brain barrier (BBB) is disturbed. According to our concept, the glio-vascular relationships and thus the control of the BBB are essentially dependent on the polarity of astroglial cells. This polarity is characterized by the uneven distribution of the water channel protein aquaporin-4 (AQP4), dystroglycan and other molecules. Recently, we were able to show that the extracellular matrix component agrin is important for the construction and localization of the so-called orthogona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 45 publications
6
73
0
Order By: Relevance
“…Loss of macroglial polarization – characterized by depletion of molecules that normally are enriched in macroglial endfoot membranes - emerges as a prominent feature of a number of diseases and disease models, including temporal lobe epilepsy, Alzheimer’s disease, stroke, injury, and glioblastoma (Eid et al, 2005; Yang et al, 2011; Noell et al, 2012; Zeynalov et al, 2008; Robel et al, 2011). Losing polarity implies loss of normal function.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of macroglial polarization – characterized by depletion of molecules that normally are enriched in macroglial endfoot membranes - emerges as a prominent feature of a number of diseases and disease models, including temporal lobe epilepsy, Alzheimer’s disease, stroke, injury, and glioblastoma (Eid et al, 2005; Yang et al, 2011; Noell et al, 2012; Zeynalov et al, 2008; Robel et al, 2011). Losing polarity implies loss of normal function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the blood-tumor barrier is leaky compared to the healthy, intact bloodbrain barrier, which helps supply the tumor with an increasing demand of nutrients. 284,285 Noell et al 286 showed increased MMP-2, -3, and -9 immunoreactivity in brain slices of human primary glioblastomas compared to non-tumor brain tissue and assumed blood-brain barrier leakage in this area. Studies from other groups detected increased proMMP-2 and proMMP-9 levels in the CSF of dogs with intracranial tumors compared to healthy dogs.…”
Section: Brain Cancermentioning
confidence: 99%
“…Increased expression of AQP4 or Aqp4 mRNA has been found in numerous conditions, including bacterial meningitis (141), inflammation secondary to intraparenchymal injection of lipopolysaccharides (LPS) (187) or lysolecithin (190), subarachnoid hemorrhage (198), intracerebral hemorrhage (182), brain tumors (32,135,164), and hydrocephalus (100,144,168,170,189). It is still not known whether changes in surface expression of AQP4 occur under physiological conditions.…”
Section: Regulationmentioning
confidence: 99%